VARIABILIDAD EN RASGOS POLINICOS EN EL COMPLEJO MIMULUS LUTEUS L. (PHRYMACEAE) EN CHILE CENTRAL - Carvallo, Gastón; Ginocchio, Rosanna (Gayana Botánica, 2004)
We quantified the variability of pollen morphology and life history traits among three natural populations of two taxa in the Mimulus luteus complex and a group of putative hybrids that coexist in the Andean ranges of central Chile. Pollen grain production and polar/equatorial length ratio, an index of pollen grain morphology, differed significantly among the taxa. The differences detected in these generally conservative traits, may reflect introgression, known to be common in Mimulus.